1993
DOI: 10.1212/wnl.43.2.338
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella (Q fever)‐associated myelopathy

Abstract: We describe six men with a slowly progressive myelopathy characterized by asymmetric, incomplete spinal cord syndrome manifested with a thoracic sensory level, mild spastic paraparesis, and urinary incontinence. The spinal cord lesions were evident by MRI in four of them. Coxiella burnetii infection was confirmed in the blood of all patients by immunofluorescence microscopic assay (IFA) and transmission electron microscopy (TEM). In two patients, we detected C burnetii by TEM and IFA using CSF from the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our team has recently demonstrated that C. burnetii infection is associated with an increased risk of lymphoma (334). Before that study, 22 cases of lymphoproliferative disease in the context of Q fever were available in the literature (621)(622)(623)(624). A patient who was followed in our center for a C. burnetii vascular infection was diagnosed with B-cell lymphoma, and C. burnetii was detected in the lymphoma tissue.…”
Section: Other Related Clinical Syndromesmentioning
confidence: 99%
“…Our team has recently demonstrated that C. burnetii infection is associated with an increased risk of lymphoma (334). Before that study, 22 cases of lymphoproliferative disease in the context of Q fever were available in the literature (621)(622)(623)(624). A patient who was followed in our center for a C. burnetii vascular infection was diagnosed with B-cell lymphoma, and C. burnetii was detected in the lymphoma tissue.…”
Section: Other Related Clinical Syndromesmentioning
confidence: 99%
“…The potential of C. burnetii triggering CNS immune reactivity has first been noted in two reports documenting the development of optic neuritis in the course of Q-fever [7,8]. The potential tropism of C. burnetii (or its accompanying immunological reactions) to the spinal cord is further substantiated by one single report of chronic myelopathy associated with Q-fever [3]. Here, in six patients with slowly progressive myelopathy C. burnetii was demonstrated by culturing the agent from peripheral blood lymphocytes.…”
Section: Letter To the Editorsmentioning
confidence: 95%
“…Partial recovery or the arrest of further neurologic deterioration was seen after treatment with appropriate antibiotics. However, the detection of the organism in the CSF succeeded in only 2 of the 6 reported cases [3]. Normal CSF findings are typical for Q-fever [6].…”
Section: Letter To the Editorsmentioning
confidence: 95%
“…The typical clinical manifestations are a self‐limited febrile illness with fatigue, chills and headaches, atypical pneumonia, hepatitis and endocarditis (1). Neurologic complications are rare and range from meningoencephalitis, cerebellitis, extrapyramidal signs, myelopathy, optic neuritis to Guillain Barré syndrome and Miller Fisher syndrome (1–7).…”
mentioning
confidence: 99%